Interspinous spacer versus traditional decompressive surgery for lumbar spinal stenosis: a systematic review and meta-analysis. - Ai-Min Wu; Yong Zhou; Qing-Long Li; Xin-Lei Wu; Yong-Long Jin; Peng Luo; Yong-Long Chi; Xiang-Yang Wang (PLoS ONE)
Background Dynamic interspinous spacers, such as X-stop, Coflex, DIAM, and Aperius, are widely used for the treatment of lumbar spinal stenosis. However, controversy remains as to whether dynamic interspinous spacer use is superior to traditional decompressive surgery. Methods Medline, Embase, Cochrane Library, and the Cochrane Controlled Trials Register were searched during August 2013. A track search was performed on February 27, 2014. Study was included in this review if it was: (1) a randomized controlled trial (RCT) or non-randomized prospective comparison study, (2) comparing the clinical outcomes for interspinous spacer use versus traditional decompressive surgery, (3) in a minimum of 30 patients, (4) with a follow-up duration of at least 12 months. Results Two RCTs and three non-randomized prospective studies were included, with 204 patients in the interspinous spacer (IS) group and 217 patients in the traditional decompressive surgery (TDS) group. Pooled analysis showed no significant difference between the IS and TDS groups for low back pain (WMD: 1.2; 95% CI: -10.12, 12.53; P = 0.03; I2 = 66%), leg pain (WMD: 7.12; 95% CI: -3.88, 18.12; P = 0.02; I2 = 70%), ODI (WMD: 6.88; 95% CI: -14.92, 28.68; P = 0.03; I2 = 79%), RDQ (WMD: -1.30, 95% CI: -3.07, 0.47; P = 0.00; I2 = 0%), or complications (RR: 1.39; 95% CI: 0.61, 3.14; P = 0.23; I2 = 28%). The TDS group had a significantly lower incidence of reoperation (RR: 3.34; 95% CI: 1.77, 6.31; P = 0.60; I2 = 0%). Conclusion Although patients may obtain some benefits from interspinous spacers implanted through a minimally invasive technique, interspinous spacer use is associated with a higher incidence of reoperation and higher cost. The indications, risks, and benefits of using an interspinous process device should be carefully considered before surgery.